2022
DOI: 10.3389/fpsyg.2022.804363
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Support and Proactive Innovation Behavior: The Mediating Role of Basic Psychological Needs

Abstract: Drawing upon self-determination theory, this study aimed to explore the mechanisms underlying the impact of perceived organizational support on proactive innovation behavior and reveal the serial mediation effects of basic psychological needs. We collected time-lagged data of 481 employees from research institutions in China, and structural equation modeling analyses were carried out to test the hypotheses. The results indicate that perceived organizational support is significantly and positively related to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
1
10
0
1
Order By: Relevance
“…We adopted the structural equation modeling technique using the Analysis of Moment of Structures (AMOS) software version 24.0 (Fan et al, 2022). Before testing the hypothesized relationships of this study, calculations were made to check the reliability, convergent, and discriminant validity among the multi-item constructs as well as common method variance and variance inflation factor analysis to ascertain the levels of response bias and multicollinearity issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopted the structural equation modeling technique using the Analysis of Moment of Structures (AMOS) software version 24.0 (Fan et al, 2022). Before testing the hypothesized relationships of this study, calculations were made to check the reliability, convergent, and discriminant validity among the multi-item constructs as well as common method variance and variance inflation factor analysis to ascertain the levels of response bias and multicollinearity issues.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior analytical techniques, the structural equation modeling was used to test the hypotheses in this study (Arkorful and Lugu, 2021;Fan et al, 2022). All indexes met acceptable standards (χ 2 /df = 2.386, IFI = 0.967, NFI = 0.930, TLI = 0.961, CFI = 0.967, GFI = 0.901, RMSEA = 0.048).…”
Section: Hypothesis Testingmentioning
confidence: 93%
“…Proactive innovation behavior (PIB) is an extra-role behavior, which refers to the process in which employees actively and positively improve their work environment and voluntarily and put corresponding efforts into the innovative activities (Fan et al, 2022). It shown that proactive behavior is often based on communication with others and is more dependent on a good organizational climate (Haynie et al, 2017; Wu et al, 2018).…”
Section: Background Literature and Research Hypothesesmentioning
confidence: 99%
“…A work climate in which the employees feel supported can enhance their performance, particularly on exploratory activities (Deci et al, 2001). When employees perceive the support for innovation from organizations, they would return the favor from organizations by doing well in innovation-role behavior (Fan et al, 2022). In an organizational innovation climate, people are allowed to handle unexpected issues proactively and to make decisions even in situations where they lack information and certainty in the workplace (Isaksen and Ekvall, 2010).…”
Section: Organizational Innovation Climate As a Moderatormentioning
confidence: 99%